PENGARUH AROMATERAPI ESSENTIAL LEMON TERHADAP PENURUNAN EMESIS GRAVIDARUM PADA IBU HAMIL DI PMB ROSITA KOTA PEKANBARU - Diana Rifka Yulia Wahyuni; Emi Yulita; Putri Indra Gandi; Ekki Noviana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Emesis gravidarum is a common condition experienced by pregnant women, especially during the first trimester, and may interfere with daily activities. Lemon essential oil aromatherapy is one of the non-pharmacological therapies used to reduce nausea and vomiting during pregnancy. This study aimed to determine the effect of lemon essential oil aromatherapy on reducing emesis gravidarum among pregnant women at PMB Rosita, Pekanbaru City. This study used a quasi-experimental design with a pre-test and post-test approach. The sample consisted of 40 pregnant women experiencing emesis gravidarum. Data were analyzed using the paired sample t-test. The results showed that before the intervention, the majority of respondents experienced mild emesis gravidarum, with 32 respondents (80%). After receiving lemon essential oil aromatherapy, the number increased to 37 respondents (92.5%). Statistical analysis showed a significance value (2-tailed) of 0.00 (p 0.05), indicating a significant effect of lemon essential oil aromatherapy on reducing emesis gravidarum. In conclusion, lemon essential oil aromatherapy is effective in reducing emesis gravidarum among pregnant women and can be used as a safe non-pharmacological therapy.Keywords: Lemon Essential Oil, Emesis Gravidarum, Pregnant Women, Aromatherapy.